The Ethics of Developing, Implementing, and Using Advanced Warehouse Technologies: Top-Down Principles Versus The Guidance Ethics Approach - Hosseini, Ziagul; Nyholm, Sven; Le Blanc, Pascale M. (Journal of Human-Technology Relations, 2024)
Advanced technologies are increasingly being utilised in logistics warehouses, raising ethical concerns about responsible development, implementation, and use. In this study, we follow Verbeek's guidance ethics approach to explore the potential positive and negative effects of advanced technologies on the quality of work and values considered important by key stakeholders. This bottom-up approach led us to conduct 23 interviews with engineers, technology advisors, employees with managerial tasks, and operators who are designing, implementing, and/or using advanced technologies. We identified nine categories of technology effects on society, warehousing companies’ business, and operators’ work (i.e., economic, health, opportunities for development, job autonomy, technical complexity, employee voice in technology implementation, job (in)security, privacy, and societal effects). However, limitations were observed in relying on this bottom-up approach, as most stakeholders displayed minimal reflection on ethics and did not formulate their responses in terms of values. To address this, we propose a combination of top-down ethical guidelines and this bottom-up approach, which is essential for evaluating and justifying decision-making throughout the development, implementation, and use of advanced technologies. By combining bottom-up stakeholder engagement and top-down ethical considerations, a more holistic approach to the ethical integration of advanced technologies in logistics warehouses can be achieved.